PENGARUH KEPATUHAN WAJIB PAJAK, PROFESIONALISME ACCOUNT REPRESENTATIVE, DAN APLIKASI E-TAX TERHADAP PENERIMAAN PAJAK KPP PRATAMA TULUNGAGUNG - Ihda Riyadlotul Khatwa; Afifudin Afifudin; Siti Aminah Anwar (Universitas Islam Malang, 2020)
ABSTRACT The purpose of this study was to determine the effect of Taxpayer Compliance, Professional Representative Accounts, E-Tax Applications on Tax Receipts at KPP Pratama Tulungagung. This type of research is quantitative research by case study. The population used is individual taxpayers registered in KPP Pratama Tulungagung. Samples taken using the Slovin formula. The method used is quantitative with multiple analysis techniques with descriptive analysis, and partial or simultaneous hypothesis testing to determine the effect of each variable. The research results showed that taxpayer compliance and account representative professionalism affected tax revenue, while e-tax applications did not affect tax revenue.Keywords: taxpayer compliance, account representative professionalism, e-tax application, Tax revenue